Life in Extreme Environments Diversity, Adaptability and Valuable Resources of Bioactive Molecules - Najjari, Afef (IntechOpen, 2023)
This book focuses on how organisms survive in extreme conditions and the role of bioactive molecules in their adaptation to these environments. With their wide and versatile metabolic and enzymatic diversity, coupled with extraordinary physiological capacities, these enzymes and metabolites have been exploited to develop clean and sustainable industrial processes. Additionally, antibiotics, compatible solutes, and other compounds obtainable from these microbes are finding a variety of uses. We undertook this editorial project to make valuable contributions available to the research and academic community interested in extremophile adaptations and interactions under extreme environments. The editor is confident that the chapters in this book will be of interest to the research community.